Pengembangan Bahan Ajar Berbasis Web Bermuatan Cerita Rakyat Rokan Hulu untuk Siswa SMA Kelas X - Anisa Fitri; Firman Santosa (Universitas Muhammadiyah Jember, 2025)
Folklore is a cultural heritage that can be used as a means of disseminating the values of character education to the younger generation. The research aims to produce web-based teaching materials containing Rokan Hulu folklore which is full of character education values for class X high school students. The research method used is research and development of the ADDIE model. This research was conducted at SMA N 1 Rambah, SMA N 3 Rambah, and SMA N 3 Rambah. This research involved 81 class X students from the high school, 3 Indonesian language teachers, and Rokan Hulu cultural figures. The folk tales used as material in this e-module are folk tales from Rokan Hulu, totaling 8 folk tale titles. The results of the folklore analysis obtained 12 types of character education values. The development of teaching materials containing folklore and the character education values contained therein was realized in the form of a web-based electronic module, entitled E-module Indonesian Language Wisdom of Folklore: Exploring Character Education in Narrative Texts. The results of the e-module feasibility test based on content/material aspects, linguistic aspects, and graphic/presentation aspects obtained an average of 92.2% with a very feasible category. The results of student responses to the e-module obtained a result of 83,21% which indicated that the e-module was very feasible.